Aglomerasi Industri Kelautan melalui Penataan Zonasi Kawasan Strategis Nasional Bima dan Sumbawa Andalan - Sitti Hilyana; Soraya Gigentika; Endiena Bulan Mutiara Sani; Ummu Kultsum (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
The Strategic Areas of Teluk Bima and Teluk Saleh on Sumbawa Island have potential natural resources for regional economic development. Through the determination of the Teluk Bima and Teluk Saleh areas as National Strategic Areas, it is expected that economic growth in this region will develop significantly, so that regulations are needed from the aspects of planning, utilization and control of space to support various infrastructure activities and other sector activities in the context of realizing a safe, comfortable space, productive and sustainable. This study aims to analyze the suitability of space as a national strategic area. Data was collected through library research and searching for data and information on institutions related to the FGD approach. Space suitability analysis using Geographic Information System (GIS) approach. The results show that the Teluk Bima Bay and Teluk Saleh area (called Bima and Sumbawa Andalan) is worthy of being a national strategic area, with the leading sectors of tourism, industry and fisheries, so that it is important to prepare the Spatial Planning of the Strategic area.